Optimizing the Role of Cadres in Increasing the Coverage of Early Detection of Cervical Cancer in the Working Area of Dasuk Health Center - Fariansyah, Irham; Istata, Marita Dony; Nuarita, Rusliyana; Samsuri, Samsuri; Nurhayati, Titik; Septiani, Tri Asih (Journal of Community Engagement in Health, 2024)
Cancer is a public health problem in the world. Cancer can threaten health both physically and psychologically and can even cause death. One of the cancers that most often causes death in women is cervical cancer. Efforts to prevent cervical cancer with the cervical cancer screening program in 2018 found estimated data on the number of cervical cancer cases in East Java Province of 27,837 which has the largest number of cervical cancer sufferers compared to other provinces. Meanwhile, 2020 experienced obstacles due to the co-19 pandemic. The COVID-19 pandemic has had a major impact on cervical cancer screening. Based on the data results from the 2022 Dasuk Health Center Performance Assessment Report, the total target of WUS (Women of Reproductive Age) in the Dasuk Health Center Work Area is 6. 672 targets. While the number of WUS (Women of Reproductive Age) who carried out early detection of cervical cancer through the IVA method was 438 targets (0.06%). This shows that the awareness of women of childbearing age in conducting early screening for cervical cancer is still low. Identification of factors that influence the low coverage of early detection of cervical cancer in the Working Area of ​​the Dasuk Health Center with fishbone diagram analysis and identification of priority problems with ultrasound analysis shows that the problems that need to be prioritized for resolution are campaign discontinuity, people are afraid to check IVA tests, lack of public understanding of the importance IVA test examination.